Critical Review: The Negative Impacts of Social Media-Induced Fear of Missing Out (FoMO): Online Stalking, Social Comparison, and Digital Fatigue - Akbar Nur Aziz; Azam Syukur Rahmatullah (Universitas PGRI Yogyakarta, 2025)
The purpose of this article is to analyze in depth the criticism of the negative impact of social media addiction which gives rise to FoMO attitudes. This research uses a critical observation method with a qualitative descriptive approach, with a focus on in-depth analysis of the methodology, conclusions and discussion of the main article. The main reference comes from the article entitled